Mongolia : Technical Assistance Report-Report on the Prices Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Mongolia regarding updating and improving the consumer price index (CPI) and the industrial producer price index (IPPI). The IMF mission recommends an adjustment to the expenditure shares in the updated CPI based on alternative data sources and improvements to the compilation procedure used to estimate the monthly price change for automobiles and motorcycles. The selection of enterprises and products in the rebased IPPI should ensure appropriate coverage of exports. The mission also recommends that this process include a review of 2015 customs data to ensure that relevant enterprises and their products are selected in proportion to their significance to overall production.